Workers’ remittance, real exchange rate and economic growth in labour-exporting Asian countries - Ngoma, Abubakar Lawan (2015)
Workers’ remittances have been identified as a significant and stable source of foreign exchange earnings for migrants’ source developing countries. At the regional level,Asia accounts for more than 63 per cent of all global workers’ remittance flows. The officially recorded inflows of workers’ remittances to the labour-sending Asian countries were estimated to reach US$260 billion in 2012. Workers’ remittances contributed more than five times official development assistance in the region. Countries such as India, China, the Philippines, Pakistan, Bangladesh and Lebanon, depend considerably on workers’ remittances as a source of foreign exchange and stimulant for macroeconomic stability. However, little empirical evidence is established on the determinants and economic impact of workers’ remttances in the region. Theoretical considerations suggest that the flows of workers’ remittances may have important long-run implications on real exchange rate appreciation and economic growth in remittance-receiving developing countries. However, empirical studies documented on these issues have produced inconclusive evidence due to omitted variable bias and measurement issues. Most existing studies disregard the impact of financial development and institutional quality in estimating the determinants and longrun growth effect of workers’ remittances. Also, the presence of multicolinearity in analysing the interaction effects of workers’ remittances and these variables has led to ambiguous results. In view of these problems, this research is set to reexamine these issues via three objectives while using orthogonalised interaction effects, which provide solution to the multicolinearity problem and Pooled Mean Group (PMG) estimator on panel data from 18 labour-sending Asian countries over the period of 1981-2010. The first objective examined the impact of domestic macroeconomic conditions on the inflows of migrant workers’ remittances. The finding of the study revealed significant evidence on the impact of domestic macroeconomic factors on the inflows of workers’ remittances. In particular, factors such as interest rate differentials between the migrant home and destination countries, exchange rate depreciation and financial sector development in the recipient countries, favourably induce remittance flows from overseas working migrants. Conversely, workers’ remittances respond negatively to domestic economic uncertainty and institutional quality in remittance-receiving Asian countries. The second objective considered the long-run impact of workers’ remittances on real exchange rate appreciation, while accounting for the mitigating impact of financial development. Using both external and internal measures of real exchange rate, the research found significant evidence on the long-run impact of workers’ remittances on real exchange rate appreciation in remittance-receiving Asian countries. However, the effect varies with the level of financial sector development. Higher level of financial intermediation in remittance-receiving countries have been observed to diminish the appreciation of real exchange rates brought about by high inflows of workers’ remittances. The third objective investigated the long-run impact of workers’ remittances on economic growth, while accounting for the interactive effects of financial development and institutional quality. The result of the study showed significant evidence of the long-run positive impact of workers’ remittances on economic growth in remittancereceiving Asian countries. Workers’ remittances promote long-run growth regardless of the presence of quality institutions and financial sector development in these countries. Moreover, the existence of strong financial system, which funnels workers’ remittances into productive investments, complements the growth impact of workers’ remittances in the recipient countries. Conversely, better institutions undermine the use of workers’ remittances for growth enhancing economic activities in remittance-receiving Asian countries. The findings from this study suggest that migrant-sending Asian countries with competitive macroeconomic conditions and relatively weak institutional environment received higher inflows of workers’ remittances than their counterparts. Also, persistent inflows of workers’ remittances can raise the prices of non-traded goods, thereby leading to long-run real exchange rate appreciation and loss of export competitiveness. However, this adverse effect can be rectified if the development of the financial sector in these countries has the capacity to channel remittance income into productive investments. In addition, workers’ remittance has the potential to generate long-run economic growth in remittance recipient Asian countries. The growth impact will be even more pronounced in countries with a higher level of financial development but relatively lower institutional quality.